In Search of Excellence : Lessons from America's Best-Run Companies - Peters, Thomas J. and Waterman, Robert H. (GHQ,Rawalpindi Army Education Press, 1982)
Discusses eight basic practices characteristic of successfully managed companies.
Includes Notes and Index
Keywords: Industrial Management -- United States -- Management--Technique -- Management -- Organizational Effectiveness